Cardiogenic shock in Non-ST elevated AMI patients in a rural tertiary care hospital in Eastern India - Shyamal Kanti Pal; Debasis Sarkar; Liton Sarkar; Ramtanu Bandyopadhyay (International Journal of Medical Research and Review, 2017)
Introduction: Acute Myocardial infarction is one of the leading causes of morbidity and mortality worldwide. Cardiogenic Shock is the leading cause of death in patients hospitalised for acute MI. Although there is substantial evidence for a benefit of reperfusion therapy for ST elevation MI, the best treatment strategy for patients with non-ST segment elevated MI is less well defined. Outcome and prognosis differs with the presence or absence of ST segment elevation. Most of the studies have been done on urban population.Objective: To determine the frequency and profile of Non-ST elevated MI. Any differences in profile in a Rural population with different social and economic structure will also be documented.Methods: In this descriptive cross-sectional study conducted in Medicine department, Malda Medical College & Hospital, WestBengal, India 100 patients of non STEMI are selected by using consecutive non probability sampling technique. After taking ethical clearance from Institution and consent from patients and their relatives, 100 patients of non STEMI are enrolled as per inclusion and exclusion criteria. They are evaluated for cardiogenic shock on the basis standard clinical examination and are managed as per protocol. All relevant data are recorded in predesigned proforma.Results: Out of 100 patients, 68 are male and 32 are female. Mean age of the patients is 60 + 1.26 years and majority of them are in the age group of 61-70 years(41%). 5% patients of non STEMI developed cardiogenic shock and majorities are male and more than 50% of patients with cardiogenic shock with non STEMI are above 70 years old.Conclusion: Frequency and Profile is comparable to other studies. This rising trendin a rural population of a developing country is due to probably more urbanisationrelated to change in food habits and life style changes.